IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PERTAMBANGAN - Jhon Nasyaroeka (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
The Company is an entity engaged in a commercial corporation that involved many peopleincluding shareholders. stakeholders. Where do they have their own interests. But in a company theyhave the same goal which is to get a high value of the company. In many corporate businessactivities to improve corporate value them by revealing corporate social responsibility (CSR). Withthe company's conduct and disclose CSR activities can affect the value of the company.The results of this study indicate that the disclosure Coroprate Social Responsibility (CSR)effect on firm value. which has been proved by the classical assumption test (normality test,autocorrelation, multikolonieritas test, test heterocedastisity) with significant results. And tested witha regression model (test determinants, the test statistic F, the test statistic t) with the result that theCorporate Social Responsibility (CSR) effect on firm value.